2009
DOI: 10.1542/peds.2008-3582
|View full text |Cite
|
Sign up to set email alerts
|

Can Association Between Preterm Birth and Autism be Explained by Maternal or Neonatal Morbidity?

Abstract: The increased risk of autistic disorders related to preterm birth is mediated primarily by prenatal and neonatal complications that occur more commonly among preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
179
1
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(200 citation statements)
references
References 33 publications
12
179
1
7
Order By: Relevance
“…A 2009 metaanalysis found a positive association between maternal gestational diabetes and ASD. 100 Since then, there have been conflicting findings, 102,124,139,141,144,145 although some of these studies did not differentiate between prepregnancy and gestational diabetes.…”
Section: Parental Agementioning
confidence: 99%
See 1 more Smart Citation
“…A 2009 metaanalysis found a positive association between maternal gestational diabetes and ASD. 100 Since then, there have been conflicting findings, 102,124,139,141,144,145 although some of these studies did not differentiate between prepregnancy and gestational diabetes.…”
Section: Parental Agementioning
confidence: 99%
“…Five studies 125,144,[209][210][211] and two systematic reviews 13,157 investigated this risk factor. According to the systematic reviews, hyperbilirubinemia was associated with an increased risk of autism 13,157 with a summary effect estimate of 1.87 (95% CI: 1.01-3.47), according to the meta-analysis.…”
Section: Neonatal Jaundicementioning
confidence: 99%
“…However, epidemiological findings have not consistently found evidence of increased ASD risk with infection. For example, a California study of 407 ASD cases reported that hospitalization with infection was associated with increased risk (Zerbo et al, 2013), while a Swedish study of 1,216 ASD cases found no such evidence (Buchmayer et al, 2009), In order to build the evidence base concerning prenatal infection and ASD risk, additional epidemiological studies are necessary. Moreover, as different subtypes of ASD may have different environmental components (Frazier et al, 2014), it is important to examine whether prenatal infection differentially influences ASD subtype risk (with or without intellectual disability).…”
Section: Introductionmentioning
confidence: 99%
“…A prospective study of all births less than 26 weeks gestation in 1995 in the United Kingdom and Ireland concluded that expreterm children are at increased risk for ASD in middle childhood, compared with their term-born classmates, after psychiatric, clinical, IQ and SCQ (Social Communication Questionnaire) evaluations (Johnson et al, 2010). A cohort of 164 families with autistic children (Brimacombe et al, 2007) concluded that the increased risk of autistic disorders related to prematurity is primarily attributed to perinatal complications that occur more commonly among preterm infants, results also confirmed in a Swedish population-based case-control study (Buchmayer et al, 2009). A meta-analysis on prenatal risk factors for autism argued that evidence is insufficient to implicate individual prenatal factors in autism etiology, because many of the studies examined all available prenatal data using designs with methodological weaknesses, so that significant associations may have been observed by chance after multiple testing (Gardener et al, 2009).…”
Section: The Role Of Prematuritymentioning
confidence: 84%